The Timing of Surgery and Symptom Resolution in Patients Undergoing Transforaminal Lumbar Interbody Fusion for Lumbar Degenerative Disk Disease and Radiculopathy. Issue 6 (July 2017) - Villavicencio, Alan T.; Nelson, E. Lee; Rajpal, Sharad; Burneikiene, Sigita
Abstract : Objective: Success rates of surgical interventions for lumbar disorders vary significantly depending on multiple factors and, among them, the duration of symptoms. It is not clear whether there is a "cutoff" time when decompression and fusion surgery becomes less effective in the conditions with chronic nerve root compression symptomatology. The main objective of this study was to analyze whether duration of symptoms has any effect on clinical outcomes and primarily resolution of radicular pain symptoms due to degenerative disk disease and stenosis with spondylolisthesis in patients undergoing transforaminal lumbar interbody fusion (TLIF). Methods: The prospective observational study was performed. Eighty-four patients with radicular symptoms due to degenerative disk disease and stenosis with spondylolisthesis with no previous fusion surgeries and undergoing 1- to 3-level TLIF surgery were enrolled. Fifteen patients (18%) were lost to follow-up and were excluded from this analysis leaving a total of 69 patients. Standardized questionnaires were used to analyze clinical outcomes and were administered preoperatively within 3 months of scheduled surgery, and postoperatively at 3, 6, 12, and 24 months. To emphasize the change in clinical outcome scores, the relevant scores were calculated as the ratio of minimal clinically important difference values and change scores. The change scores were calculated by subtracting the postoperative scores from the baseline scores. Multiple regression analyses were conducted to examine the relationship of the duration of symptoms and relevant minimal clinically important difference ratio values while controlling for independent variables. Further, a comparison between 2 groups of patients was performed to analyze the changes of clinical outcomes for the patients who underwent fusion within <24 months versus ≥24 months. Results: It was determined that the duration of symptoms was a significant predictor of better leg pain resolution ( P =0.018), but not back pain resolution ( P =0.27), or improvement in ODI ( P =0.10) and SF-36 PCS scores ( P =0.19). The patients with shorter duration of symptoms had significantly better radicular symptom resolution ( P =0.032) compared with patients who waited at least 24 months or longer to undergo fusion. Conclusions: A shorter duration of symptoms was found to be a statistically significant predictor for better resolution of radicular symptoms in patients undergoing TLIF for painful degenerative disk disease and stenosis with spondylolisthesis.